Silicon Nitride/Silicon Dioxide Echelle Grating Spectrometer for Operation Near 1.55 μm - Shengjie Xie; Yang Meng; Joss Bland-Hawthorn; Sylvain Veilleux; Mario Dagenais (IEEE Photonics Journal, 2018)
Here we use an electron beam lithography system to pattern an ${\rm{S}}{{\rm{i}}_{3}}{{\rm{N}}_{4}}{\rm{/Si}}{{\rm{O}}_{2}}$ echelle grating using silver as a reflector on the grating grooves. The grating in this letter achieves 1.39 dB on-chip loss, a spectral resolution of ∼1300, a 1.2 dB channel nonuniformity, and less than −30 dB adjacent channel crosstalk for the transverse electric field polarization. We establish that stitching errors can lead to appreciable adjacent channel crosstalk if proper precaution is not taken to minimize them.